PENDIDIKAN AGAMA ANAK SUKU KALANG - Zulfa E., Misbah (WALISONGO, 2011)
Abstract This study with descriptive qualitative approach produces a fact that the context of education, the children of the kalang community in general are also followed formal education, like other school children. They also received religious instruction as a compulsory subject. This of course has consequences for the possibility of cultural transformation through the instrument of education. Especially with religious education, the children of the Kalang community possible simultaneously and slowly will leave their teachings. Moreover, the nature of religious education itself is more of an orthodox religious values. *** Kajian dengan pendekatan deskritif ini menyajikan fakta bahwa konteks pendidikan, anak-anak suku Kalang secara umum mengikuti pendidikan formal, sebagaimana anak-anak lain pada umumnya. Mereka juga menerima pelajaran agama sebagai pelajaran wajib. Hal ini tentu saja berpengaruh terhadap kemungkinan terjadinya transformasi budaya melalui instrumen pendidikan. Khususnya terkait dengan pendidikan agama, anak-anak suku Kalang dimungkinkan secara simultan dan perlahan akan meninggalkan ajarannya. Apalagi model pendidikan agama yang mereka terima adalah pendidikan yang lebih banyak memuat nilai-nilai ortodoks. Keywords: pendidikan, agama, budaya, suku Kalang BIBLIOGRAFI Abdullah, Prof. Dr. Irwan, Konstruksi dan Reproduksi Kebudayaan. Yogyakarta: Pustaka Pelajar, 2006. Abuddin Nata, Peta Keragaman Pemikiran Islam Di Indonesia, Jakarta, Rajawali Pers, 2001. Amin Abdullah, Islam Normatifitas dan Historisitas, Yogyakarta, Pustaka Pelajar, 1999. Antlov, Hans dkk., Kepemimpinan Jawa, Perintah Halus Pemerintahan Otoriter, Yayasan Obor Indonesia, Jakarta, 2001. Barth, Fredrik, Ethnic Groups and Boundaries: The Social Organization of Culture Difference, Bergen: Waveland Press, 1998. Beatty, Andrew, âAdam and Eve and Vishnu: Syncretism in the Javanese Slametanâ dalam The Journal of Anthropological institute 2 (Juni, 1996). Bocock, Robert, Pengantar Komprehensif untuk Memahami Hegemoni, terj. Ikramullah Mahyuddin, Yogyakarta: Jalasutra, 2007. Elizabeth, Misbah Zulfa, âMulti-etnisitas Indonesia dan Potensi Konflik di Dalamnyaâ dalam Mediasi dan Resolusi Konflik di Indonesia (Musahadi, ed.), Semarang: Walisongo Mediation Center, 2007. Geertz, Clifford, Abangan, Santri, Priyayi dalam Masyarakat Jawa, Jakarta: Pustaka Jaya, 1981. Hefner, Robert W., Hindu Javanese: Tengger Tradition an Islam, Princenton: Princeton University Press, 1985. Ibnu Qoyim Ismaâil, Religi Lokal dan Pandangan Hidup, Jakarta: Penerbit LIPI, Pusat Penelitian Kemasyarakatan dan Kebudayaan, Jakarta, 2004. Joel, Kahn, Culture, Multiculture, Postculture, London: SAGE Publication, 1995. Koentjaraningrat, Pokok-pokok Antropologi Sosial, Jakarta: Gramedia, 1999. __________, Pengantar Ilmu Antropologi, Jakarta: Rineka Cipta, 2002. __________, Manusia dan Kebudayaan di Indonesia, Jakarta, Djambatan, 2002. Kwak, Kyunghwa, âAdolescents and Their Parents: A Review of intergenerational Family Relations for Immigrant and Non-Immigrant Familiesâ dalam Human Development, Kingstone: Queenâs University, 2003. Misbah Zulfa E. Pendidikan Agama Anak Suku Kalang 464 Walisongo, Volume 19, Nomor 2, November 2011 Lindholm, Charles, Culture and Identity: The History, Theory, and Practice of Psychological Anthropology, Oneworld Publications, 2007. Muhadjir, Noeng, Metode Penelitian Kualitatif, Yogyakarta: Rake Sarasih, 1996. Muhaimin AG, Islam dalam Bingkai Budaya Lokal Potret dari Cirebon, Jakarta: Logos, 2001. Mujiran, Paulus, Republik Para Maling, Pustaka Pelajar, Jogjakarta, 1998. Mulder, Niel, Agama, Hidup Sehari-Hari dan Perubahan Budaya, Jakarta: Gramedia Pustaka Utama, 1999. Musahadi, dkk., Nalar Islam Nusantara, Jakarta: Diktis Depag RI, 2008. Nakamura, Bulan Sabit di Atas Pohon Beringin/The Crescent Arises Over The Banyan Tree, Yogyakarta: Gadjah Mada University Press, 1974. Nakamura, Mitsuo, Bulan Sabit Muncul dari Balik Pohon Beringin, Jogyakarta: UGM Press, 1983. Nurcholish Madjid. Konsep dan Pengertian Akhlak Bangsa (Indonesia di Simpang Jalan), Jakarta: Mizan., 1998. Nordholt, Nico Schule, Ojo Dumeh: Kepemimpinan Lokal dalam Paguyuban Pedesaan, Jakarta: Pustaka Sinar Harapan, 1987. Pierre Bourdieu and Jean Claude Passeron, Reproduction in Education, Society and Culture, revised edition, New York: SAGE, 1990. Rahman, Fazlur, Islam dan Modernitas, edisi terj., Bandung: Pustaka, 1994. Raharjo, Slamet, Lagu Dolanan Jawa (Solmisasi). PGRI Krida karya. Semarang Sujamto, Otonomi, birokrasi, Partisipasi. Semarang: Dahara Prize, 2002. Said, Edward, Orientalism, London: Routledge & Kegan Paul, 1978. Setiadi, Elly M, dkk. Ilmu Sosial dan Budaya Dasar, Jakarta: Kencana, 2006. Sholeh, Ahmad, Upacara Obong, Tesis S2, PPS IAIN Walisongo 2004. Stuart Hall, âCultural Identity and Diasporaâ dalam J. Rutherford (ed), Identity, Community, Culture, Difference, London: Lawrence and Wishart, 1990. Suara Merdeka, 31 Januari 2008. Sulardjo Pontjosutirto, âAntropologi Orang Kalang,â hasil penelitian FH UGM, 1971. Sutirman Eka Ardhana, Wong Kalang âMembangun Diri dengan Budaya Bisnis,â 2003. Syamsuddin, âTujuan Pendidikan Agama,â makalah dalam Workshop Metodologi Pengajaran Agama SMP, 15-18 September 2005 di Banten. Walisongo, Volume 19, Nomor 2, November 2011 465 Tilaar, H.A.R., Education, Culture, and The Indonesian Civil Society: Indonesian Education Reform Policies for the Third Millennium, Jakarta: Remaja Rosdakarya, 1999. __________, Kekuasaan dan Pendidikan, Suatu Tinjauan dari Perspektif Studi Kultural, Jakarta: Penerbit Indonesia Tera, 2003. Tim Puspar UGM, Wawasan Budaya untuk Pembangunan; Menoleh Kearifan Lokal, Yogyakarta: Pilar Politika. 2004. Yekti Maunati, Identitas Dayak: Komodifikasi dan Politik Kebudayaan, Jogyakarta: LKiS, 2006. Woodward, Mark R., Islam in Jawa: Normative Piety and Mysticism in The Sultanate of Yogyakarta, An Arbor: UMI, 1989.